Administration of TNF- Inhibitors for Rheumatoid Arthritis Therapy. Comments to the Results of a Meta-Analysis of Randomized Trials by N. Graudal et al.: Final or Thought Provoking Conclusions? - Mikhail M. Kostik ("Paediatrician" Publishers LLC, 2016)
.